The role of smoking history in longitudinal changes in C-reactive protein between Black and White older adults in the US - Nancy C. Jao; Aresha Martinez-Cardoso; Moin Vahora; Marcia M. Tan (Preventive Medicine Reports, 2022)
Smoking cessation is associated with decreases in C-reactive protein (CRP), a biomarker of systemic inflammation and cancer risk; yet CRP levels remain higher long-term in individuals who quit vs. those who never smoked. While non-Hispanic, Black/African American (NHB) have higher levels of CRP vs. non-Hispanic, White/Caucasian (NHW) adults, the association between CRP and race has not been examined in individuals with smoking history. Utilizing longitudinal data from the Health and Retirement Study (HRS), the current study examined the effects of race and smoking history on CRP in older adults. NHB (n = 242) and NHW (n = 1529) participants completed HRS assessments in 2006, 2010, and 2014. Dried blood spots collected at each wave were assayed for CRP. Linear mixed models were used to examine the effect of race and smoking history on CRP across waves – controlling for sociodemographics, physical activity, body mass index (BMI), and current smoking. Overall, results showed no significant effects of race or current smoking on CRP; rather age, sex, education, BMI, physical activity, smoking history, and time × race predicted CRP (ps<.04). However, while age, sex, education, BMI, physical activity, and smoking history were also predictive of CRP in NHWs (ps<.04) in race-stratified models, only BMI was a significant predictor of CRP in NHBs (p=.012). BMI may be important in explaining inflammation-related disease risk in NHBs with a history of smoking. NHBs may not experience the same reductions in CRP with smoking cessation as NHWs – potentially contributing to tobacco-related health disparities.